Determinan Penggunaan E-Money pada Mahasiswa Program Studi Akuntansi - Pangestu Miftahul Wahid Azis; Sulistyowati Erna (Masyarakat Ekonomi Syariah Bogor, 2024)
This article discusses the use of QRIS e-money among accounting study program students at the National Development University